Protective Factors in Forensic Practice: The Added Value of the SAPROF-Extended Version Pilot in Relation to Aggressive Incidents - Cappon, Leen (Criminal justice and behavior, 2023)
Protective factors are now commonly included in comprehensive risk assessment. This study concerns an initial validation of the new SAPROF-Extended Version (SAPROF-EV) pilot, containing modifications and additions to the original SAPROF. For 139 forensic psychiatric inpatients, assessment results with the SAPROF-EV pilot and HCR-20V3 were compared with aggressive incidents. Results show good predictive validity for the SAPROF-EV pilot for all outcomes and incremental predictive validity for both the (modified) original SAPROF and the full SAPROF-EV pilot over the HCR-20V3. For the outcome aggression toward others, the additional SAPROF-EV factors provide incremental predictive validity over the (modified) original SAPROF. In addition, the user feedback from clinicians highlights experienced additional value of the new factors for treatment guidance. Based on the findings from this study, the SAPROF-EV pilot will be adjusted further into an improved and enhanced version of the SAPROF.